1980
DOI: 10.1007/bf00540195
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of biomass of species differing in photosynthetic pathway along an altitudinal transect in southeastern wyoming grassland

Abstract: Based on the physiological characteristics and responses of C, C, and CAM plants to environmental factors, it is generally predicted that C and CAM plants will become more abundant with increasing temperature and decreasing precipitation. To test this prediction, the relative contribution of each photosynthetic type to total plant community biomass was examined at seven study areas along an altitudinal transect in southeastern Wyoming grassland. In going from high (2,652 m) to low (1,405 m) elevation along thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
54
0
1

Year Published

1983
1983
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(56 citation statements)
references
References 30 publications
1
54
0
1
Order By: Relevance
“…Seed mass data were compiled from the KEW Royal Botanic Garden Seed Information Database (Royal Botanic Gardens Kew 2016, http://data.kew.org/sid/), and consist of average weight in grams per 1000 seeds. Photosynthetic pathways (C3 or C4) were not found for all species, but if another species in the same genus was available, we assumed the same pathway for the species of interest (Syvertsen et al 1976;Doliner and Jolliffe 1979;Waller and Lewis 1979;Boutton et al 1980).…”
Section: Trait Datamentioning
confidence: 99%
“…Seed mass data were compiled from the KEW Royal Botanic Garden Seed Information Database (Royal Botanic Gardens Kew 2016, http://data.kew.org/sid/), and consist of average weight in grams per 1000 seeds. Photosynthetic pathways (C3 or C4) were not found for all species, but if another species in the same genus was available, we assumed the same pathway for the species of interest (Syvertsen et al 1976;Doliner and Jolliffe 1979;Waller and Lewis 1979;Boutton et al 1980).…”
Section: Trait Datamentioning
confidence: 99%
“…As long as there is sufficient diversity of microsites at a given locale, both C 3 and C 4 species could coexist. Temporal separations of C 3 and C 4 plants in communities have been measured and found to be significant in Wyoming (Boutton et al 1980), Colorado (Kemp and Williams 1980), and South Dakota (Ode et al 1980). These studies found C 3 species to be dominant, in either biomass or frequency, in the spring.…”
Section: Introductionmentioning
confidence: 95%
“…Multivariate analyses of the abundance of C 3 and C 4 grasses and herbs of North America have indicated that high moisture availability and low temperatures are strong correlates of relative C 3 abundance (Teeri and Stowe 1976;Stowe and Teeri 1978). Large-scale elevational transects in Wyoming (Boutton et al 1980), Kenya (Tieszen et al 1979), and Costa Rica (Chazdon 1978) show, with increasing elevation, a transition from C 4 to C 3 as the predominant photosynthetic pathway. Both drought stress and temperature tend to decrease with increasing elevation in these studies.…”
Section: Introductionmentioning
confidence: 97%
“…[3] Under constant atmospheric CO 2 concentration, dominance of the different photosynthetic pathways to a community is climate-dependent [Teeri and Stowe, 1976;Stowe and Teeri, 1978;Teeri et al, 1980;Boutton et al, 1980;Epstein et al, 1997;Sage et al, 1999]. Modern C3 plant dominates in the high latitude forest, tundra and most temperate grassland, while the C4 plant are most abundant in hot, semiarid environments with high light intensity such as grasslands, savannas, deserts and salt marshes, CAM plants are only important in some desert environment.…”
mentioning
confidence: 99%
“…[4] Among the climatic variables, temperature is a predominant determinant on the distribution of modern C3 and C4 vegetation around the world [Teeri and Stowe, 1976;Stowe and Teeri, 1978;Teeri et al, 1980;Boutton et al, 1980;Epstein et al, 1997], while precipitation is believed to play only a secondary role [Sage et al, 1999]. Therefore a linkage between the isotope signature of SOM and temperature is presumably a priori owing to the plant propagation.…”
mentioning
confidence: 99%